Warming appears as the main risk of non-adaptedness for western Mediterranean relict fir forests under expected climate change scenarios - Méndez-Cea, Belén; García-García, Isabel; Linares, Juan Carlos; Gallego, Francisco Javier (Frontiers in Plant Science, 2023)
Circum-Mediterranean firs are considered one of the most drought-sensitive species to climate change. Understanding the genetic basis of trees adaptive capacity and intra-specific variability to drought avoidance is mandatory to define conservation measures thus potentially prevent their extinction. We focus here on Abies pinsapo and Abies marocana, both relict tree species, endemic from south Spain and north Morocco, respectively. A total of 607 samples were collected from eight nuclei; six from Spanish fir and two from Moroccan fir. A genotyping by sequencing technique called double digestion RAD-seq (ddRAD-seq), was performed to obtain a genetic matrix based on single nucleotide polymorphisms (SNPs). This matrix was utilized to study the genetic structure of A. pinsapo populations and to carry out selection signatures studies. In order to understand how Spanish fir and Moroccan fir cope with climate change, genotype-environment associations (GEA) were identified. Further, the vulnerability of these species to climate variations was estimated by the risk of non-adaptedness (RONA). The filtering of the de novo assembly of A. pinsapo provided 3,982 SNPs, from 504 out of 509 trees sequenced. PCA genetically separated Grazalema from the rest of the Spanish populations. However, FST values showed significant differences among the sampling points. We found 51 loci potentially under selection. Homolog sequences were found for some proteins related to abiotic stress response, such as dehydration-responsive element binding transcription factor, regulation of abscisic acid signaling, and methylation pathway. A total of 15 associations with 11 different loci were observed in the GEA studies, being the maximum temperature of warmest month the variable with the highest number of associated loci. This temperature sensitivity was also supported by the risk of non-adaptedness, which yielded the higher risk for both A. pinsapo and A. marocana under the high emissions scenario (RCP 8.5). This study sheds light on the response to climate change of these two endemic species.